Targeting HMGB1 ameliorates cardiac fibrosis through restoring TLR2-mediated autophagy suppression in myocardial fibroblasts. (15th September 2018) - Wu, Ri-Na; Yu, Tian-Yu; Zhou, Ji-Chao; Li, Meng; Gao, Hui-Kuan; Zhao, Can; Dong, Rui-Qing; Peng, Dian; Hu, Zhuo-Wei; Zhang, Xiao-Wei; Wu, Yong-Quan
Abstract: Background: Extracellular high-mobility group box 1 (HMGB1) has been identified as playing a critical role in the pathogenesis of tissue fibrosis. However, the underlying mechanism of its involvement in cardiac fibrosis is still not well-defined. Here, we aim to investigate whether toll-like receptor 2 (TLR2) contributes to the extracellular HMGB1-mediated development and progression of cardiac fibrosis. Methods: A mouse model of cardiac fibrosis was induced by subcutaneous injection of isoproterenol (ISO). Glycyrrhizic acid (GA), an inhibitor of HMGB1 derived from natural products, was simultaneously administered by intraperitoneal injection. Echocardiography, H&E and Sirius red staining were used to evaluate cardiac function and fibrosis. The myocardial expression of autophagy-associated proteins was examined using immunoblotting. Cardiac fibroblasts were treated with different concentrations of HMGB1 to examine the expression levels of α-SMA, collagen I and autophagy markers. Interactions of HMGB1/TLR2 and α-SMA/p62 were examined by immunoprecipitation and immunofluorescence. Results: ISO-treated mice showed characteristic cardiac fibrosis, increased expression and co-localization of HMGB1 and TLR2, as well as impaired autophagic signals in myocardial tissues, which could be prevented by silencing TLR2. Exogenous administration of HMGB1 blocked the autophagic flux in fibroblasts, which caused extensive accumulation of collagen I and α-SMA. In addition, cardiac fibrosis was alleviated by GA treatment through abrogating the interaction between HMGB1 and TLR2. Conclusions: Our study suggests that the interaction between TLR2 and HMGB1 contributes to the pathogenesis of cardiac fibrosis via suppressing fibroblast autophagy, and that inhibiting HMGB1 with GA provides therapeutic benefits for the treatment of fibroproliferative heart diseases. Highlights: Cardiac fibrosis is the major determinant of morbidity and mortality in patients with heart diseases and there are no effective anti-fibrotic agents to prevent or even reverse cardiac fibrosis. We identified that TLR2-contributed to the pathogenesis of cardiac fibrosis by mediating extracellular HMGB1-triggered autophagy suppression in cardiac fibroblasts, and demonstrated that inhibiting HMGB1 with glycyrrhizic acid (GA), an inhibitor of HMGB1, protected against ISO-induced cardiac fibrosis through restoring autophagy activity in fibroblasts. Our study provides a novel view that targeting both HMGB1-TLR2 signaling and impaired autophagic flux in heart are promising therapeutic strategies for the treatment of fibroproliferative heart diseases.